2014
DOI: 10.1155/2014/256519
|View full text |Cite
|
Sign up to set email alerts
|

Fall-Related Emergency Department Admission: Fall Environment and Settings and Related Injury Patterns in 6357 Patients with Special Emphasis on the Elderly

Abstract: Principals. Throughout the world, falls are a major public health problem and a socioeconomic burden. Nevertheless there is little knowledge about how the injury types may be related to the aetiology and setting of the fall, especially in the elderly. We have therefore analysed all patients presenting with a fall to our Emergency Department (ED) over the past five years. Methods. Our retrospective data analysis comprised adult patients admitted to our Emergency Department between January 1, 2006, and December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 23 publications
(36 reference statements)
1
11
0
Order By: Relevance
“…In another study on the circumstances of falls among patients age 75 and older in an emergency department, more falls were reported indoors at home but, similar to our study, with a lower risk of severe injury [42]. A potential explanation is that falls at home may not involve further hazards that may cause additional injury [42].…”
Section: Discussionsupporting
confidence: 81%
“…In another study on the circumstances of falls among patients age 75 and older in an emergency department, more falls were reported indoors at home but, similar to our study, with a lower risk of severe injury [42]. A potential explanation is that falls at home may not involve further hazards that may cause additional injury [42].…”
Section: Discussionsupporting
confidence: 81%
“…It has been found, however, to have a high mortality rate and a long duration (days) of hospitalization, and the patients in the present study were no exception (Table 2) [1,2,[6][7][8][11][12][13][14]. Taylor et al [15] investigated the effect of age on mortality among patients hospitalized for blunt injury and reported that the mortality rate increased with age, being 5.2% among those aged 65 to 74 years, 6.7% among those aged 75 to 84 years, and 9.22% among those aged 85 years or older.…”
Section: Discussionmentioning
confidence: 47%
“…Our study showed that our patients were more likely to experience their most recent fall at home rather than outside the home. While we could not find any other study assessing this finding in older patients with cancer, prior studies on community-dwelling older adult populations have shown that most falls, especially in frail people, happen at home [ 20 , 21 ]. This is likely due to older frail patients spending more time at home.…”
Section: Discussionmentioning
confidence: 60%